1990
DOI: 10.1103/physrevb.42.5481
|View full text |Cite
|
Sign up to set email alerts
|

Amorphization along interfaces and grain boundaries in polycrystalline multilayers: An x-ray-diffraction study of Ni/Ti multilayers

Abstract: Diffusion-induced solid-state amorphization (SSA) was studied in (fcc Ni)/(hcp Ti) multilayers at 523 K. The multilayers had a modulation length of 24.4 nm and an overall composition of Ni4OTi«.They were polycrystalline without coherency between the Ni and Ti sublayers. The phase changes, composition changes, and strain development were studied for annealing times up to 220 h, primarily using x-ray-diffraction methods. Upon annealing, an amorphous phase developed, concurrently with dissolution of Ti in crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(49 citation statements)
references
References 15 publications
7
42
0
Order By: Relevance
“…This indicates that an amorphous layer was formed in each interfacial region by inter-diffusion of Ti and Ni. Similar solid state amorphization phenomenon between Ti and Ni has been also reported by previous researches [12][13][14][15][16][17][18][19][20]. Based on the above results, it is considered that the first exothermic peak in a DSC curve is due to the reaction for the solid state amorphization.…”
Section: Resultssupporting
confidence: 50%
“…This indicates that an amorphous layer was formed in each interfacial region by inter-diffusion of Ti and Ni. Similar solid state amorphization phenomenon between Ti and Ni has been also reported by previous researches [12][13][14][15][16][17][18][19][20]. Based on the above results, it is considered that the first exothermic peak in a DSC curve is due to the reaction for the solid state amorphization.…”
Section: Resultssupporting
confidence: 50%
“…(1) and the data described above, for a series of g values (see Figure 7(a)). It follows that at diffusion lengths larger than the diffusion lengths of the current study (i.e., k > 7 nm), an effect of a variation of k onD (i.e., interdiffusion in regime (ii) and not in regime (iii)) is only expected for viscosities of g > 1 Â 10 13 Pa s, which is larger than the measured values for the viscosity of amorphous Ni-Zr at 400 C. 119 The viscosity of a liquid can be estimated according to the Stokes-Einstein equation…”
Section: Diffusion-induced Stress Effects On Interdiffusion In Thementioning
confidence: 98%
“…9,10 Furthermore, during interdiffusion of polycrystalline thin films an amorphous solid solution can be formed. [11][12][13][14][15][16][17][18] In many applications, Zr-based metallic glasses are used due to their high glass forming ability. Several factors determine the glass forming ability, such as the enthalpy of mixing, size difference of the elemental components, energies of the interfaces between the amorphous and crystalline phases as well as long range diffusivity.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, grain boundaries and dislocations are theoretically recognized here as preferable places for nucleation of the amorphous phase; this corresponds to experimental data [7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…In experimental studies the role of defects has been revealed to be very important in amorphization phenomena in crystals. In particular, it has been experimentally observed that the amorphous phase commonly nucleates at interphase and (inter)grain boundaries [7][8][9] and, sometimes, at interfacial and lattice dislocations [10,11]. In order to take into account the important role of defects in the solid-state amorphization, several theoretical models have been proposed describing such amorphization micromechanisms as the splitting of disclinations at triple junctions of grain boundaries [12,13], special diffusion-induced grain boundary migration [14], amorphization in regions with high-density ensembles of point defects [15,16], and deformation-induced splitting of grain boundaries intersected with pile-ups of lattice dislocations [17].…”
Section: Introductionmentioning
confidence: 99%